Pemanfaatan Dadap Serep (Erythirna Subumbrans Merr) Sebagai Alternatif Penanganan Bendungan Asi Pada Ibu Menyusui - Dechoni Rahmawati; Ristiana Eka Ariningtyas (Yayasan Daarul Huda Kruengmane, 2023)
Argorejo Village is one of the villages in Bantul. Based on preliminary studies in Argorejo village, there are mothers who are breastfeeding experiencing breast milk dams. Mothers who experience breast milk dams do not know the benefits of Dadap Serep (Erythirna Subumbrans Merr) as an alternative to handling breast milk dams in mothers who are breastfeeding. Armed with an understanding of the content in the natural ingredients of the Dadap Serep plant (Erythirna Subumbrans Merr), it is hoped that breastfeeding mothers who experience breast milk dams in the working area of the Sedayu 2 Health Center can be handled properly. This community service aims to find out the knowledge of breastfeeding mothers about the natural benefits of the Dadap Serep plant (Erythirna Subumbrans Merr) as an alternative to handling breast milk dams in mothers who are breastfeeding. The implementation of this activity is carried out in three stages, namely preparation, implementation, and reporting. The preparation phase includes obtaining permits, preliminary studies, collecting materials, and preparing tools and materials, as well as coordination with related parties. The stage of implementing the activity is to carry out service counseling face-to-face with participants. The evaluation stage is carried out by evaluating the results of participants' knowledge about the benefits of spare dadap (Erythirna Subumbrans Merr) as an alternative to handling breast milk dams in breastfeeding mothers The output of this service is in the form of promotional media, namely leaflate.